Factors Associated With Time to Achieve Employment Through Occupational Support Programs in Patients With Mood Disorders: 1 Year Naturalistic Study - Hayasaka, Tomonari; Takaesu, Yoshikazu; Nagashima, Izumi; Futada, Miku; Nozaki, Kazuhiro; Katagiri, Takeshi; Imamura, Yayoi; Kurihara, Mariko; Oe, Yuki; Tsuboi, Takashi; Watanabe, Koichiro (Frontiers in Psychiatry, 2021)
Objective: Mood disorders cause significant work performance disability in sufferers and often lead to adverse employment outcomes in working individuals. The aim of this study was to explore factors associated with time to achieve employment through the occupational support program (OSP) for patients with mood disorders. Methods: The participants were patients admitted to the Kyorin university hospital from April 2016 to April 2019. Patients who met the criteria for major depressive disorder and depressive episode of bipolar I or II disorder according to DSM-5 and participated in the occupational therapy-based OSP for at least 3 sessions (1 course) were included in this study. We collected demographic and clinical variables at the baseline of this study through medical records and OSP records; the variables included age, gender, diagnosis, scores of Quick Inventory of Depressive Symptomatology and Global Assessment of Functioning, the number of times of participation in the OSP, word count of the transcription task in the OSP, typographical deficiency, fatigue status and mood status after the OSP. The primary outcome was set as the time to achieve the employment within one year after the discharge. Results: Of the 211 patients who participated in the OSP during the survey period, 49 participants met the criteria in this study. The results showed that 14 patients achieved and the other 35 patients did not achieve the employment within one year of discharge from the hospital. A multivariate cox regression analysis revealed that the word count of the transcription task in the OSP (HR=1.03, 95% CI=1.01–1.05, p=0.016) and mood status after the OSP (HR=2.77, 95% CI=1.18–6.51, p=0.019) were significantly associated with time to achieve the employment. Conclusion: In conclusion, this study suggested that work speed and mood response in the OSP could be significant predictors for achieving employment in patients with mood disorders.